Mechanical behavior of carbon-reinforced thermoplastic sandwich composites with several core types during three-point bending tests. (15th April 2021) - Harizi, Walid; Anjoul, Joey; Acosta Santamaría, Victor A.; Aboura, Zoheir; Briand, Valérie
Abstract: The originality of this paper is the study of the bending behavior of several carbon-fiber-reinforced thermoplastic sandwich composites under three-point bending tests using a mechanical-acoustic experimental coupling approach. The skins were fabricated from thermoplastic Polyphenylsulfone "PPSU" resin reinforced by 2 × 2 twill desized carbon fabrics. Different core materials (Nomex, Aluminum and Polyetherimide PEI) with different topologies (honeycomb, straight tubular and inclined tubular at 15°) and two densities (48 and 64 kg/m 3 ) are used for the manufacturing of the different sandwich panels. During the bending tests, a laser device measured the deflection, two acoustic emission transducers evaluated the acoustic activity and a video-microscope monitored the damage evolution in-situ and in real-time. Thereby, the mechanical-acoustic coupling allowed relevant monitoring of the different strain and damage mechanisms generated within the different sandwich configurations. According to this study, the aluminum core sandwich structure presents the highest stiffness. However, the thermoplastic PEI core sandwich structures show the highest ductility and absorbed energy.